Atmospheric icing at Lomnický štít - OSTROŽLÍK, Marián (Contributions to Geophysics and Geodesy, 2021)
Time series of the daily and monthly amounts of atmospheric icing at Lomnický štít covering the 1957–2003 period were used to study the seasonal variability of atmospheric icing in the high-mountain conditions. Obtained results were compared with the corresponding data from other mountain positions in the Central Europe. It was shown that at Lomnický štít there are suitable meteorological and other conditions for the accretion of atmospheric icing. The number of days with the atmospheric icing and its annual course at Lomnický štít are typical in these climatic characteristics for the corresponding mountain areas in the Central Europe. Whereas the annual courses of the number of days as well as of the mean daily amounts of atmospheric icing are relatively simple the annual course of the mean monthly amounts of atmospheric icing is not expressive